The impact of women's reproductive health on participation in the workforce: A qualitative study - Eda Yakit Ak; Özden Tandoğan (WORK: A Journal of Prevention, Assessment & Rehabilitation, 2026)
Background One of the barriers women face in participating in the workforce is reproductive health issues. Objective This study was conducted to investigate the experiences of women when they encounter reproductive health issues in the workplace. Methods The sample comprised 15 women who had experienced a women's health condition within the past 2 to 12 months and were employed in income-generating positions. Data were collected through a semi-structured interview format, with interviews conducted individually via videoconference using an in-depth interview approach. The data were analyzed using inductive thematic analysis following Braun and Clarke's six-step framework. Results The data collected from their statements were categorized into several themes: awareness of women's health, approaches to women's health problems at work, colleagues’ attitudes toward these issues, and the gender of managers regarding women's health concerns. The findings revealed that training programs aimed at improving women's health were not organized in workplaces. In situations affecting women's health, such as pregnancy, childbirth, and infertility treatment, managers generally exhibited positive attitudes. However, there was a lack of understanding regarding conditions that are not outwardly visible, such as dysmenorrhea and ovarian cysts, which led to restrictions on taking leave. Women expressed that they would feel more comfortable addressing women's health issues and would be more likely to take leave if they worked under a female manager. Conclusions There is a prevailing belief that women's health issues should not be shared, particularly when working with a male manager. Participants’ experiences suggest that female managers may facilitate safer communication around reproductive health concerns; however, supportive institutional policies, rather than manager gender alone, are likely more critical for sustainable change.